Design an Infusion Device Analyzer with Flow Rate Parameters using Photodiode Sensor - Andjar Pudji Pudji; Anita Miftahul Maghfiroh; Nuntachai Thongpance (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Infusion devices are the basis for primary health care, that is to provide medicine, nutrition, and hydration to patients. One of the infusion devices is a syringe pump and an infusion pump. This device is very important to assist the volume and flow that enters the patient's body, especially in situations related to neonatology or cancer treatment. Therefore, a comparison tool is needed to see whether the equipment is used or not. The purpose of this research is to make an infusion device analyzer (IDA) design with a flow rate parameter. The contribution of this research is that the tool can calculate the correct value of the flow rate that comes out of the infusion pump and syringe pump. The water released by the infusion pump or syringe pump will be converted into droplets which are then detected by the sensor. This tool uses an infrared sensor and a photodiode. The results obtained by the sensor will come by Arduino nano and code it to the 16x2 Character Liquid Crystal Display (LCD) and can be stored on an SD Card so that it can be analyzed further. In setting the flow rate for the syringe pump of 100 mL / hour, the error value is 3.9, 50 ml / hour 0.02, 20 mL / hour 0.378, 10 mL / hour 0.048, and 5 mL / hour 0.01. The results show that the average error of the syringe pump performance read by the module is 0.87. The results obtained from this study can be implemented for the calibration of the infusion pump and the syringe pump so that it can be determined whether the device is suitable or not